Removal of Cd2+ by hydroxyapatite adsorption granule from aqueous solution. Issue 5 (24th October 2018) - Duyen, Le Thi; Thao, Le Thi Phuong; Hai, Do Thi; Dung, Pham Tien; Nam, Pham Thi; Thom, Nguyen Thi; Hong, Cao Thi; Linh, Cao Thuy; Thanh, Dinh Thi Mai
Abstract: Hydroxyapatite (HAp) adsorption granules with average size of 2 × 10 mm was fabricated from HAp powder and polyvinyl alcohol (PVA) additive by sintering for removing of Cd 2+ ions from aqueous solution. The effect of some factors on the Cd 2+ adsorption efficiency and capacity was investigated. The removal efficiency and capacity reached 86.5 % and 4.33 mg/g, respectively, at condition: HAp granule mass of 0.3 g, initial Cd 2+ concentration of 30 mg/L, contact time of 40 minutes and pH 0 of 5.7 at 30°C. The experimental data was described by Langmuir and Freundlich isotherm models; pseudo‐first order and pseudo‐second order kinetic equations.